Five-Year Evaluation of the PROA-NEN Pediatric Antimicrobial Stewardship Program in a Spanish Tertiary Hospital - Aurora Fernández-Polo; Susana Melendo-Perez; Nieves Larrosa Escartin; Natalia Mendoza-Palomar; Marie Antoinette Frick; Pere Soler-Palacin; on behalf of the PROA-NEN Working Group (MDPI AG, 2024)
Introduction: Actions to reduce and optimize antimicrobial use are crucial in the management of infectious diseases to counteract the emergence of short- and long-term resistance. This is particularly important for pediatric patients due to the increasing incidence of serious infections caused by resistant bacteria in this population. The aim of this study was to evaluate the impact of a pediatric antimicrobial stewardship program (PROA-NEN) implemented in a Spanish tertiary hospital by assessing the use of systemic antimicrobials, clinical indicators, antimicrobial resistance, and costs. Methods: In this quasi-experimental, single-center study, we included pediatric patients (0-18 years) admitted to specialized pediatric medical and surgical units, as well as pediatric and neonatal intensive care units, from January 2015 to December 2019. The impact of the PROA-NEN program was assessed using process (consumption trends and prescription quality) and outcome indicators (clinical and microbiological). Antibiotic prescription quality was determined using quarterly point prevalence cross-sectional analyses. Results: Total antimicrobial consumption decreased during the initial three years of the PROA-NEN program, followed by a slight rebound in 2019. This decrease was particularly evident in intensive care and surgical units. Antibiotic use, according to the WHO Access, Watch and Reserve (AWaRe) classification, remained stable during the study period. The overall rate of appropriate prescription was 83.2%, with a significant increase over the study period. Clinical indicators did not substantially change over the study period. Direct antimicrobial expenses decreased by 27.3% from 2015 to 2019. Conclusions: The PROA-NEN program was associated with reduced antimicrobial consumption, improved appropriate use, and decreased costs without compromising clinical and/or microbiological outcomes in patients.